2017
DOI: 10.3390/ijms18050951
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Root Genes in Arabidopsis Seedlings Grown by Standard and Improved Growing Methods

Abstract: Roots of Arabidopsis thaliana seedlings grown in the laboratory using the traditional plant-growing culture system (TPG) were covered to maintain them in darkness. This new method is based on a dark chamber and is named the improved plant-growing method (IPG). We measured the light conditions in dark chambers, and found that the highest light intensity was dramatically reduced deeper in the dark chamber. In the bottom and side parts of dark chambers, roots were almost completely shaded. Using the high-throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…In addition, a few of studies have shown that UVR8 in cells was not fully determined by light and UV-B radiation [ 23 ]. For example, UVR8s were found in the roots of Arabidopsis and carrots, which participated in root growth and secondary metabolism [ 24 , 25 ]. In this study, the UVR8 (Unigene0003427) in the roots of M. himalaica was significantly upregulated in UV-B radiation compare with CK plants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few of studies have shown that UVR8 in cells was not fully determined by light and UV-B radiation [ 23 ]. For example, UVR8s were found in the roots of Arabidopsis and carrots, which participated in root growth and secondary metabolism [ 24 , 25 ]. In this study, the UVR8 (Unigene0003427) in the roots of M. himalaica was significantly upregulated in UV-B radiation compare with CK plants.…”
Section: Discussionmentioning
confidence: 99%
“…It penetrates the soil to several centimeters or is conducted by vascular tissues (Mo et al, 2015). Using an improved Petri dish culture system, in which shoots are illuminated but roots are grown in darkness, Qu et al (2017) compared the differential gene expression patterns between illuminated and shaded roots. The authors found that shading of Arabidopsis roots grown in Petri dishes affects the expression pattern of the main groups of plant photoreceptors in the roots, implying that light affects roots via photoreceptor-mediated signaling pathways (Qu et al, 2017).…”
Section: Roots Sense Light Under the Soil Surfacementioning
confidence: 99%
“…Using an improved Petri dish culture system, in which shoots are illuminated but roots are grown in darkness, Qu et al (2017) compared the differential gene expression patterns between illuminated and shaded roots. The authors found that shading of Arabidopsis roots grown in Petri dishes affects the expression pattern of the main groups of plant photoreceptors in the roots, implying that light affects roots via photoreceptor-mediated signaling pathways (Qu et al, 2017). Therefore, several experimental systems with shaded roots were suggested to mimic natural growth conditions to improve the Petri dish-based Arabidopsis culture methods (Yokawa et al, 2011, Rellá n-Á lvarez et al, 2015Silva-Navas et al, 2015;Qu et al, 2017).…”
Section: Roots Sense Light Under the Soil Surfacementioning
confidence: 99%
See 2 more Smart Citations